1998
DOI: 10.1016/s0925-4439(98)00019-2
|View full text |Cite
|
Sign up to set email alerts
|

Decreased membrane fluidity and unsaturated fatty acids in Niemann–Pick disease type C fibroblasts

Abstract: Niemann-Pick disease type C (NP-C) is an autosomal recessive disorder characterized by the sequestration and trapping of endocytosed cholesterol in lysosomes. The NPC1 gene on chromosome 18 was recently identified but its physiological function remains unknown. We have studied the lipid compositions of cultured human NP-C fibroblasts and mouse SPM-3T3 cell line derived from the C57BL/KsJ NP-C model mouse, which belongs to the same complementation group. Fibroblasts derived from apparently normal age-matched in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
45
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 36 publications
9
45
2
1
Order By: Relevance
“…Niemann-Pick C1, Normal Human Fibroblasts, and Methyl-␤-cyclodextrin Depletion/Repletion as a Model System for Altering Cellular Cholesterol Plasma Membrane Content-NPC1 fibroblasts have been shown to exhibit a marked increase in plasma membrane cholesterol content (16) and decreased membrane fluidity relative to normal human fibroblasts (16,17). Consistent with these reports, plasma membranes isolated from NPC1 fibroblasts were found to contain ϳ2-fold higher total cholesterol content relative to NHF, whereas a similar level of resident proteins (data not shown) and phospholipid content was present in both cell types (Fig.…”
Section: Diffusion Of No Across Bilayer Lipid Membranes Decreases As mentioning
confidence: 99%
See 1 more Smart Citation
“…Niemann-Pick C1, Normal Human Fibroblasts, and Methyl-␤-cyclodextrin Depletion/Repletion as a Model System for Altering Cellular Cholesterol Plasma Membrane Content-NPC1 fibroblasts have been shown to exhibit a marked increase in plasma membrane cholesterol content (16) and decreased membrane fluidity relative to normal human fibroblasts (16,17). Consistent with these reports, plasma membranes isolated from NPC1 fibroblasts were found to contain ϳ2-fold higher total cholesterol content relative to NHF, whereas a similar level of resident proteins (data not shown) and phospholipid content was present in both cell types (Fig.…”
Section: Diffusion Of No Across Bilayer Lipid Membranes Decreases As mentioning
confidence: 99%
“…Within the plasma membrane, cholesterol segregated with sphingolipids and selective proteins form distinct lipid raft complexes that act as ordered platforms for communicating signals into and out of cells (12). Dysregulation of cholesterol synthesis and transport acts as a contributing factor to pathophysiological changes (13)(14)(15)(16)(17), which are of particular importance in cardiovascular disease, chronic inflammation, and lipid disorders such as NiemannPick disease. The influence of cholesterol on NO diffusion was directly quantified in liposomal and artificial bilayer preparations.…”
mentioning
confidence: 99%
“…The increased cholesterol impaired insulin signaling and was restored following cholesterol depletion (24). In other studies cholesterol levels have been reported to be increased, decreased, or unchanged (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 86%
“…Rhodopsin (Rh1) is required not only for transducing the light signal in the adult retina but also for stabilizing the actin-based cytoskeletal scaffold of developing photoreceptors, which is called the rhabdomere terminal web (RTW). In ninaE 117 mutants, which lack Rh1, the RTW is not organized and rhabdomere biogenesis is defective. Newly eclosed flies show inappropriately formed rhabdomeric components that involute into the cytosol [62].…”
Section: Sphingolipids In Endocytosis and Exocytosismentioning
confidence: 99%
“…Tissues derived from these mice show increased sphingomyelin content and increased ratios of saturated fatty acid to unsaturated fatty acids. These effects are accompanied by decreased plasma membrane fluidity [117].…”
Section: Microdomains and Membrane Integritymentioning
confidence: 99%